IMPLEMENTASI KEBIJAKAN PERTAMBANGAN MINERAL DAN BATUAN DI KECAMATAN BANAWA KABUPATEN DONGGALA - Hambali, Hambali (Katalogis, 2016)
The purpose of this study is: To know and analyze the implementation of of mineral and coal mining policy are not optimal. The The main theory William Dunn policies used as reference the theory of Van Meter and Van Horn examines the six aspects that is standards and policy goals, resources, characteristics of the executing agency, the attitude tendency (disposition), Activities Implementation & Communication across organizational, economic, social, and political. The place of research in Banawa District of Donggala with 7 informant selected by purposive. Data Collection by interview, observation and documentation. Data were analyzed using an interactive model of Miles and Huberman. Based on the research result that the Implementation of Mineral and Coal Mining in the district of Donggala Banawa general management of mining has the potential to serve as the mining areas were comfortable and safe for the community, government and business. However Implementation rock mining in districts of Banawa seen from six aspects everything is not optimal, thath is (1) Standards and targeted policies that appear on the lack of coordination or cooperation between the government and society (2) Resources are inadequate views of human resources and infrastructure ; while the aspect (3) Communication between organizations; which government and society have not been created through technology (4) karkateristik implementing agencies, policy rock mining and pattern of relations with the implementing agency of the other establishments inadequate (5) The conditions of economic, social, and political, informants consider not optimal (6) Disposition, the basically rock mining in the District Banawa not optimal, citizens have not changed and the positive economic developments, since mining of rock began to grow, along with that family life has not improved.